Microcuásares como fuentes de rayos cósmicos - Escobar, Gastón Javier (2021)
It is currently accepted that supernova remnants are the main sites where galactic cosmic rays undergo acceleration. Though this picture is energetically sustentable, the models predict spectra that do not match observations. On the other hand, the contribution of other kind of sources to the galactic cosmic-ray population is still unclear, and deserves investigation. In this work we explore a novel mechanism through which microquasars might produce cosmic rays, based on the generation of relativistic neutrons in situ, which escape and decay outside. Protons and electrons created in neutron decays escape to the interstellar medium as cosmic rays. The proposed mechanism produces more energetic cosmic rays from microquasars than those presented by previous works. The spectral index agrees well with that required to explain the spectral signatures of Galactic cosmic rays. Best scenarios arise in the most luminous, slow jets, which produce a cosmic-ray power, by source, comparable to that of supernova remnants. The mechanism explored in this work may provide stronger cosmic-ray sources in the early universe, and therefore contribute to the heating and reionization of the intergalactic medium.